Appropriation of an Activity-based Flexible Office in daily work - Babapour, Maral; Karlsson, MariAnne; Osvalder, Anna-Lisa (Nordic Journal of Working Life Studies, 2018)
In recent years, there has been growing interest in collaborative consumption of office environments and thereby implementation of Activity-based Flexible Offices (A-FOs). Relocating to an A-FO introduces a desk-sharing policy as well as a multitude of new workspaces with different speech policies into the employee’s work context. This paper describes how employees appropriate desk-sharing and speech policies in an A-FO. The data were collected over a period of 6 months in a case organization by means of 18 shadowing sessions. The different ways in which employees appropriated the A-FO solution were (i) adopting, experimenting with, or rejecting the desk-sharing policy, and (ii) modes of interaction arising from spatial configuration and redefining speech policies. The discussion outlines the reasons behind appropriation or nonappropriation of the desk-sharing and emergent speech policies. The insights from this study provide support for organizations considering A-FOs to develop strategies for facilitating individuals’ work in these settings.